2016
DOI: 10.2147/cia.s109004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Master’s curriculum for elderly nursing: a qualitative study

Abstract: BackgroundImproving the quality of health care and rehabilitation for the elderly is one of the most important priorities of the health care system. Given the importance of evaluating the strengths and weaknesses of any program after its implementation, this study was conducted to identify the advantages and weaknesses of a geriatric nursing program at Tehran University of Medical Sciences.MethodsThis was a qualitative study, and the study population comprised students, graduates, and professors of geriatric n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Additionally, evaluation is an essential step in the building of a curriculum or program [ 17 20 ]. As one of the earliest training courses in China, it is necessary to conduct an evaluation of the training program [ 21 ]. This paper describes the process and evaluation of the training, including satisfaction assessment, self-ratings of knowledge and skills, and a follow-up interview of application after 3 months of the course.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, evaluation is an essential step in the building of a curriculum or program [ 17 20 ]. As one of the earliest training courses in China, it is necessary to conduct an evaluation of the training program [ 21 ]. This paper describes the process and evaluation of the training, including satisfaction assessment, self-ratings of knowledge and skills, and a follow-up interview of application after 3 months of the course.…”
Section: Introductionmentioning
confidence: 99%
“…A study reported that students’ motives for choosing gerontological nursing as a field of study were their motivation to have a higher degree, their motivation to have better access to more career advancement opportunities, and the greater likelihood of successfully passing the entrance exam of the gerontological nursing master’s course. These motives result in superficial learning and limited competence for elderly care [ 43 ]. Routine-based practice was the other subcategory of the students’ neglectfulness towards learning main category in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As diverse competencies are required across different areas of health care, the presented instrument could be used to assess whether each nursing student has developed the right competencies to provide high‐quality geriatric care. These competence evaluations could also be used to develop education; for example, evidence from numerous evaluations may highlight that a nursing curriculum should focus on certain skills necessary in geriatric care (Ghaffari et al., 2016; Hsieh & Chen, 2018).…”
Section: Introductionmentioning
confidence: 99%